1998
DOI: 10.1046/j.1365-2591.1998.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of irrigant combinations within dentinal tubules

Abstract: The aim of this study was to investigate sodium hypochlorite (with and without EDTA), chlorhexidine, and hydrogen peroxide in varying concentrations when used in sequence or in combination as endodontic irrigants. Sterile saline served as the control. Six standardized bovine incisor root specimens, which had been infected with Enterococcus faecalis (CG 110), were exposed to each solution. Following exposure to the test agents dentine samples were taken from within the lumina using ISO 023 to 035 burs. The dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 0 publications
2
64
0
Order By: Relevance
“…17 A further criterion for this choice was that it also played a part in numerous other studies, so there is a comparability. 3,[6][7][8][9]12,13,15,16,21,22 According to Moritz et al, this bacterium only begins to show strong morphologic cell damage at an output of 1.5 W and 15 Hz when irradiated with an Nd:YAG laser through a 1-mm-thick layer of dentin. 15 Figure 9 shows the laser treatment of the dentin slices.…”
Section: Methodsmentioning
confidence: 99%
“…17 A further criterion for this choice was that it also played a part in numerous other studies, so there is a comparability. 3,[6][7][8][9]12,13,15,16,21,22 According to Moritz et al, this bacterium only begins to show strong morphologic cell damage at an output of 1.5 W and 15 Hz when irradiated with an Nd:YAG laser through a 1-mm-thick layer of dentin. 15 Figure 9 shows the laser treatment of the dentin slices.…”
Section: Methodsmentioning
confidence: 99%
“…14,15 In vitro studies have also been inconsistent in their findings, with NaOCl more effective, [16][17][18] chlorhexidine more effective, 8 or no significant difference between the two. [19][20][21][22][23][24] In vitro effects of NaOCl-particularly in high concentrations-on single-species or multispecies bacterial biofilms have been shown to be superior to chlorhexidine. 17,[25][26][27] However, a study revealed that chlorhexidine was more effective than NaOCl against fungi in both pure and mixed cultures as well as in biofilms.…”
mentioning
confidence: 99%
“…Successful cleaning entails the use of instruments to mechanically remove dentin, irrigant to flush loosened debris away, and chemicals to dissolve contaminants from inaccessible regions 2) . Sodium hypochlorite and hydrogen peroxide are common endodontic irrigants that are used for the debridement and deproteinization of mechanically prepared, smear-layer-covered radicular dentin 3) . Sodium hypochlorite is also frequently used for chemomechanical caries removal and the arrest of hemorrhage in pulpal exposures before bonding to coronal dentin occurs [4][5] .…”
Section: 국문초록mentioning
confidence: 99%